Long-lasting agony and failure to provide assistance in a case of mixed methadone-prescription drugs acute intoxication. (September 2021) - Giorgetti, Arianna; Natanti, Alice; Giorgetti, Raffaele; Buscemi, Loredana
Highlights: The duration of agonal phase in methadone-related deaths is often unknown. Issues of failure to provide assistance and death avoidance might arise. A case of methadone with prolonged witnessed agony is presented. Agonal phase due to methadone fatal intoxication could last up to several hours. Abstract: Methadone overdoses are usually considered "slow" and avoidable deaths. Despite being frequently witnessed, the type and duration of the agonal time are rarely documented and challenging to be reconstructed. Here we report a case in which a young male was found dead in a parked car, shortly after discharge from a compulsory psychiatric treatment. Death scene investigation, clinical records collection, analysis of video recordings from surveillance cameras and private videos, post-mortem examination, GC–MS and LC-MS/MS toxicological analyses were performed and allowed to assess an acute fatal intoxication by methadone and prescription drugs. The case here-in reported is a rare example of a witnessed and recorded prolonged agonal phase due to methadone and drug intoxication, which lasted at least 12 hours. The loss of consciousness and a worsening pattern of respiratory depression, including gasping, were reported by the friends of the victim, but no one called for help, arising the suspect of failure to provide assistance. The possibility of a long-lasting agony with respiratory gasping should be considered in the evaluation of similar intoxication cases.